The influence of anemia on cardiovascular disease course - A. V. Budnevsky; E. S. Ovsyannikov; A. V. Red`ka (Кардиоваскулярная терапия и профилактика)
Anemia, defined by WHO guidelines as a decrease of hemoglobin level <130 g/L in men and 120 g/L in women, is an independent risk factor for cardiovascular diseases. Hemoglobin level decrease by 10 g/L does increase risk of death from coronary pathology. The review focuses on the key pathophysiological mechanisms of anemia relation with cardiovascular diseases, the results briefly introduced, of comparably recent studies in this field, and their significance is treated for clinical practice.